Inventarisasi Putusan Peradilan Adat Sendi sebagai Upaya Memperkuat Constitutional Culture dalam Negara Hukum Pancasila - Dicky Eko Prasetio (Jurnal Hukum Lex Generalis, 2021)
Sendi's customary law is unique in the implementation of customary justice, namely using the Kutaramanawa Dharmasastra Book and using four local officials of Sendi's customary law, namely: Cakrabuana, Adat Attorney, Pamengku, and Kasepuhan. This uniqueness is also manifested in the decision of the Sendi customary court, which should have been used as consideration for judges in court to explore the living law of the Sendi indigenous people. This research is normative legal research using a statutory approach and a conceptual approach. Primary legal materials consist of the 1945 Constitution of the Republic of Indonesia, court decisions, and laws related to customary law, then secondary legal materials consist of journal articles, books, and websites related to customary law, Sendi's customary court, as well as the concept of constitutional culture and The constitutional state of Pancasila, then non-legal materials consist of books and non-legal journal articles which support this research, such as about indigenous peoples, culture, and Pancasila. The legal issue in this research is the absence of law at the level of a law that specifically regulates indigenous peoples. The results of this study indicate that an inventory of the decisions of Sendi's customary court is necessary to internalize and externalize the values of Sendi's customary law and are needed to strengthen aspects of the constitutional culture in the constitutional state of Pancasila.